ECONOMIC EMPOWERMENT: FUTURE INVESTMENT EDUCATION FOR TUNAS HARAPAN VOCATIONAL SCHOOL STUDENTS - Nazwa Akhaza Hani; Fitriani; Nikita Adelia Syafitri; Muzayyana; Mahda Riska Yolanda (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This Community Service Program aims to enhance financial literacy and early investment interest among students of Tunas Harapan Vocational School, Langkat, as an effort to empower the younger generation economically. The program employed an educational and participatory approach through interactive lectures, demonstrations, simulations, and group discussions. The materials covered personal financial management, saving principles, and an introduction to beginner-friendly investment instruments such as savings, gold, and mutual funds. Evaluation was conducted using a one-group pretest–posttest design involving 40 students. The results indicate a significant improvement in students’ knowledge, attitudes, and interest in investment. Knowledge of investment increased from 23.9% to 95.7%, understanding of investment terminology rose from 18.3% to 96.8%, and investment interest reached 100%. These findings demonstrate that practice-based investment education is effective in shaping a visionary mindset and improving students’ readiness to face future economic challenges, while strengthening the role of KKN as a medium for community empowerment through financial education.